Individualized perioperative respiratory support as a way of preventing postoperative pulmonary complications in abdominal surgery - Kuzmenko, Tetiana; Vorotintsev, Sergiy (Journal of Education, Health and Sport, 2019)
Introduction. Indicators of postoperative pulmonary complications (PPCs) in abdominal surgery being in the range of 17% to 88%, their development leads to an increase in morbidity and mortality, an extension in the length of stay in the medical institution, as well as material costs. In recent years, there has been a clear shift in the paradigm from the prevention of death and complications caused by lungs damage the prevention of the development of the complication. Prevention of pulmonary complications should have a comprehensive approach, but there is still no clearly formulated perioperative tactic for the management of patients with moderate or high risk of trouble development and with healthy lungs, taking into account the individual peculiarities of pulmonary tissue. Objective. To create and evaluate of the effectiveness of perioperative individualized respiratory support in patients with moderate or high risk of development of postoperative pulmonary complications in abdominal surgery. Materials and methods. The study consisted of two parts. The first retrospective partcomprised analysis of the medical histories data of 45 patients, who were included in the group 1. The prospective part of the study included 47 patients of the group 2, who had perioperative individualized respiratory support, which included intraoperative protective ventilation with low tidal volume (7 ml/kg ideal body weight), individual level of positive end-expiratory pressure and using the maneuver of the recruiting of the alveoli, sessions of the incentive spirometry for 2 days prior to surgery, and continued in the first postoperative week or only postoperative. Patients of both groups were operated onthe upper abdominal organs by open procedure, operation time was more than 2 hours, all patients had an ARISCAT score ≥26 points. Postoperative pulmonary complications development (atelectasis, pneumonia, pleural efforts, hypoxemia, pneumothorax) was monitored in the groups in the first week of the postoperative period. The statistic analysis of the data was performed with using the Microsoft Excel 2013 and Statistica for Windows 6.0 programs. When comparing the groups according to the clinical outcome, the relative risk (RR) and odds ratio (OR) were determined and then confidence intervals (95 % CI) were calculated. The difference in values was considered significant at p <0.05. Results. During the first 7 days after the operation in the group of the retrospective part of the study of PPCs developed in 35 patients (78%), of which 31 patients (69%) had pulmonary atelectasis, 11 patients (24%) got pneumonia, pleural effusion was stated in 21 patients (47%) and one (2%) produced hypoxemia. In the prospective part PPCs were recorded in 11 patients (23%). Of these, 8 patients (17%) had pulmonary atelectasis, 4 (9%) got pneumonia and 5 (11%) received pleural effusion. In both groups no cases of pneumothorax were recorded. A comparison of clinical outcomes showed that patients in group 2 had a significantly lower risk of developing atelectasis in the first week after surgery than patients in group 1: RR 0.2471 (95% CI 0.1276-0.4786), p<0.0001; OR 0.0926 (95% CI 0.0345-0.2489), p<0.0001. A similar trend was observed for postoperative pneumonia (RR 0.3482 (95% CI 0.1196-1,0139), p=0.0530; OR 0.2875 (95% CI 0.0841-0.9833), p=0.0469) and pleural effusion (RR 0.2280 (95% CI 0.0940 - 0.5526), p=0.0011; OR 0,9131 (95% CI 0.0454 – 0.4074), p=0.0004). However, the risk of hypoxemia and pneumothorax in the prospective study group did not decrease if to compare with the retrospective (hypoxemia: RR 0.3194 (95% CI 0.0134 – 7.6434), p=0.4911; OR 0.03123 (95% CI 0.0124 – 7.8682), p=0.4796; pneumothorax: RR 0.9583 (95% CI 0.0194-47.3007), p=0.9829, OR 0.9579 (95% CI 0.0186 -49.3043), p=0.9829). Conclusions. Perioperative individualized respiratory support in patients with a moderate and high risk of development of postoperative pulmonary complications is an effective method for reducing the number of atelectasis, pneumonia and pleural effusion development after the upper floor of the abdominal cavity open surgical interventions.